Pulsed electromagnetic energy treatment offers no clinical benefit in reducing the pain of knee osteoarthritis: a systematic review - Callaghan Michael; McCarthy Christopher; Oldham Jacqueline (BMC Musculoskeletal Disorders, 2006)
Abstract Background The rehabilitation of knee osteoarthritis often includes electrotherapeutic modalities as well as advice and exercise. One commonly used modality is pulsed electromagnetic field therapy (PEMF). PEMF uses electro magnetically generated fields to promote tissue repair and healing rates. Its equivocal benefit over placebo treatment has been previously suggested however recently a number of randomised controlled trials have been published that have allowed a systematic review to be conducted. Methods A systematic review of the literature from 1966 to 2005 was undertaken. Relevant computerised bibliographic databases were searched and papers reviewed independently by two reviewers for quality using validated criteria for assessment. The key outcomes of pain and functional disability were analysed with weighted and standardised mean differences being calculated. Results Five randomised controlled trials comparing PEMF with placebo were identified. The weighted mean differences of the five papers for improvement in pain and function, were small and their 95% confidence intervals included the null. Conclusion This systematic review provides further evidence that PEMF has little value in the management of knee osteoarthritis. There appears to be clear evidence for the recommendation that PEMF does not significantly reduce the pain of knee osteoarthritis.